Synthesis and Characterization of New Complexes Fe(II), Co(II) and Ni(II) Ions with Azo Ligand Derived from 4-Aminoantipyrene - AL-Azawi, Khalida F; Rasheed, Rashed Taleb; Jassim, Liblab Sami (Al-Nahrain Journal of Science, 2018)
The ligand (4-(7-hydroxy-4-methylcoumarin-8-ylazo)-1-phenyl-2,3-dimethyl pyrazol-5-one 4-yl) derived from 4-aminoantipyrine and 7-hydroxy-4-methyl coumarin. The synthesized ligand was characterized by 13C, 1HNMR, FT.IR and UV-Vis spectra. Complexes of Fe(II), Co(II) and Ni(II) with the ligand were prepared in aqueous methanol with a (1:2) M:L ratio. The prepared complexes have been characterized by using flame atomic absorption, FT.IR, UV-Vis spectra as well as magnetic susceptibility and conductivity measurements. On the basis of physicochemical data octahedral geometries were attributed for the complexes.